IMPACT OF HOMEWORK ASSIGNMENT ON STUDENTS’ LEARNING - Songsirisak, Prommin; Jitpranee, Jutharat (Journal of Education and Innovation, 2018)
Homework has become an important issue for primary and secondary schools for over five decades. Although it has both academic and non-academic purposes, only a few studies have been investigated at the tertiary level. This study investigated the impacts of homework on students’ learning. Participants were 140 undergraduates from a Thai university. A set of questionnaires and focus group interviews were used. Findings revealed that homework benefited and supported students’ learning although it had some psychological impacts on their learning and affected free time management. It enabled students to acquire knowledge, developed learning skills, and increased academic achievements. Also, it promoted student’s collaborative skills and speaking between teachers and students for homework clarification. Findings further indicated that internet was one of the powerful tools for students’ learning and homework information. Based on the findings, this study suggests strategies and implications for teachers’ instructions and effective implementation of homework for students’ learning outside class.